Spain and the Mediterranean - Gillespie, R. author. aut Link
XIV, 226 p.
Keywords: The first comprehensive study of the Mediterranean dimension to Spain's external relations. Besides an historical overview of Spanish involvement in the Mediterranean, the book analyses how relations with Morocco and Algeria were prioritized, before a more 'global' policy was adopted, extending to the Middle East. The study demonstrates how Spain has 'Europeanized' its Mediterranean policy and acquired an influential role in the EU through the Euro-Mediterranean Partnership: a multilateral response to instability in the South.